Increased Risk of Fracture in Patients Receiving Solid Organ Transplants - Rosalind Ramsey‐Goldman; Julie E. Dunn; Dorothy D. Dunlop; Frank P. Stuart; Michaël Abécassis; Dixon B. Kaufman; Craig B. Langman; Michael H. Salinger; Stuart M. Sprague (1999)
Abstract The success of organ transplantation is related to advances in immunosuppressive therapy. These medications are associated with medical complications including bone damage. The objective of this study was to estimate and compare age, gender-specific fracture incidence between transplant recipients, and a large sample representative of the civilian noninstitutionalized United States population using the 1994 National Health Interview Survey (NHIS). This was a cohort study set in tertiary care centers. Five hundred and thirty-nine individuals who received abdominal organ and 61 heart transplants surviving at least 30 days at our institution from 1986 to 1996 were included in the study. Incident fractures were ascertained by mail, in-person interview, telephone survey, or medical record review. All fractures were verified. Organ-, age-, and gender-specific fracture numbers and rates and person-years of observation, were calculated for the transplant patients. Weighted age- and gender-specific fracture rates from the 1994 NHIS were applied to the number of person-years of observation for each organ-specific age and gender category of transplant patients to generate an expected number of fractures. The ratio of observed to expected number of fractures was used to compare fracture experience of transplant patients to that of the national sample from the 1994 NHIS. Fifty-six of 600 (9.3%) patients had at least one fracture following 1221 person-years of observation. The sites of initial symptomatic fracture were as follows: foot (n = 22), arm (n = 8), leg (n = 7), ribs (n = 6), hip (n = 4), spine (n = 3), fingers (n = 3), pelvis (n = 2), and wrist (n = 1). Fracture incidence was 13 times higher than expected in male heart recipients age 45–64 years; nearly 5 times higher in male kidney recipients age 25–44 and age 45–64 years; and 18 times and 34 times higher in female kidney recipients age 25–44 years and 45–64 years compared with NHIS data. We have shown an increased incidence of fractures and estimated the magnitude of this problem in patients undergoing solid organ transplantation. Our work defines the need for a long-term prospective study of fracture risk in these patients.